ANALISIS PENERIMAAN PAJAK HIBURAN DI KOTA MANADO - Abast, Sikfrit Herold Marines; Tinangon, Jantje; Elim, Inggriani (GOING CONCERN : JURNAL RISET AKUNTANSI, 2014)
Entertainment tax one source revenue sources used to finance the implementation of the wheels of government and the development of an area, so the area is able to implement regional autonomy mandated by the Act. The method used in this research is descriptive qualitative analysis method. The technique used in this study is to collect data information, the general picture, the problems on the Entertainment Tax Revenue Office of Manado City used to analyze and process data of the Entertainment Tax. The results of this study concluded contributions Entertainment Tax to the original local Opinions Manado is very less, so does the tax revenue growth despite Leisure Entertainment Tax increased the revenue growth but the growth rate of the index is based on entertainment tax revenue is below the average so that a predicate is not successful, in terms of Entertainment Tax receipts trend using the least squares method is expected to increase significantly the revenue coming 10 years. In order for acceptance and growth of Entertainment Tax Manado obtain good predicate index. The author suggests Manado City Revenue Service tax -based information systems to build a data base and online tax payment systems to facilitate tax authorities overseeing subject Entertainment Tax in implementing their tax obligations.